Performance Analysis of Gear Honing with Modified TI-Hourglass Worm Honing Wheel - Cai Weili; Zhang Mandong (Jixie chuandong)
According to the theories of differential geometry and gear meshing,the basic equations for involute helicoids,meshinglines and meshing boundary lines are deduced.Then using MATLAB program,the contact lines and meshing boundary are drawn.The results show that,under the condition of given the parameters of gear workpiece,the distribution of contact lines and meshing boundary lines are influenced by stagger angle and center distance,the actual contact lines are influenced by work half-angle.On the premise of meeting the strength requirements,giving the center distance called modified gear drive and choosing the reasonable stagger angle and half-angle,the honing full gear without axial feed and the well-distributed and uncrossed contact lines can be realized.The problem is solved that in order to realize full gear honing,the axial feed must be adopted with small helical angle and larger center distance must be adopted with large helical angle.